Impact of Front line Demonstrations on Sesamum Production in Panchmahal District of Gujarat - A. K. Rai, S. Khajuria , Kanak Lata, J. K. Jadav, B. S. Khadda and Rajkumar (Indian Journal of Extension Education, 2022)
..